2022
DOI: 10.3390/ijms23137396
|View full text |Cite
|
Sign up to set email alerts
|

The Analysis of a Genome-Wide Association Study (GWAS) of Overweight and Obesity in Psoriasis

Abstract: There is evidence that the concomitance of psoriasis and obesity may originate from the interplay between multiple genetic pathways and involve gene–gene interactions. The aim of this study was to compare the genetic background related to obesity among psoriatic patients versus healthy controls by means of a Genome-Wide Association Study (GWAS). A total of 972 psoriatic patients and a total of 5878 healthy donors were enrolled in this study. DNA samples were genotyped for over 500,000 single nucleotide polymor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
12
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9
1

Relationship

3
7

Authors

Journals

citations
Cited by 13 publications
(13 citation statements)
references
References 50 publications
1
12
0
Order By: Relevance
“…Psoriasis is a complex disease involving various pathogenic and immunological mechanisms ( 17 , 96 ). Although >100 psoriasis susceptibility loci have been identified through GWAS in different countries and ethnicities ( 96 101 ), there have been limited studies on genetic susceptibility loci in Taiwan ( 102 , 103 ). The present study conducted GWAS and PRS to identify 92 novel genomic markers and identified 61 previously reported genomic markers associated with psoriasis.…”
Section: Discussionmentioning
confidence: 99%
“…Psoriasis is a complex disease involving various pathogenic and immunological mechanisms ( 17 , 96 ). Although >100 psoriasis susceptibility loci have been identified through GWAS in different countries and ethnicities ( 96 101 ), there have been limited studies on genetic susceptibility loci in Taiwan ( 102 , 103 ). The present study conducted GWAS and PRS to identify 92 novel genomic markers and identified 61 previously reported genomic markers associated with psoriasis.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, the association between obesity and psoriasis has received affirmation from animal studies ( 42 ). A study that compared the genetic background of obesity in psoriasis patients with that of healthy controls through GWAS revealed a connection between 11 genetic polymorphisms and abnormal body weight in psoriasis patients ( 43 ). Findings from previous studies have also suggested that weight loss can lead to improved clinical outcomes, including a reduction in psoriatic flares ( 15 , 44 46 ).…”
Section: Discussionmentioning
confidence: 99%
“…Afterward, DNA samples underwent a PCR reaction for sex verification. The same method was performed as in our previous study [ 73 ].…”
Section: Methodsmentioning
confidence: 99%